METAPHOR: MAPPING THE CONCEPTUAL LANDSCAPE - Nguyen, Hoa; Huynh , Anh Tuan (VNU Journal of Foreign Studies, 2026)
This paper aims to sketch the current state of metaphor research, tracing its development from classical rhetoric to contemporary approaches including multimodal, cognitive, pragmatic, and critical perspectives. It outlines the theoretical foundations of metaphor and its conceptual, cultural, and communicative functions, emphasizing how metaphors, grounded in embodied experience and image schemas, both shape and reflect cognition, culture, and ideology. The discussion engages with Conceptual Metaphor Theory (CMT), Conceptual Blending Theory (CBT), Extended Conceptual Metaphor Theory (ECMT), and Critical Metaphor Analysis (CMA), while highlighting its cross-cultural variation and use across multiple domains. Metaphor has become a central lens for exploring how we conceptualize, interpret, and relate to the world. In addition to this global overview, the paper enriches the field with a selective review of Vietnamese metaphor studies, showcasing how Vietnam-based research contributes to the overall conceptual landscape. It argues that metaphor research now stands at an interdisciplinary crossroads. Emerging directions include examining metaphors across new modalities such as speech, sign language, gesture, film, emoji, memes, and advertising, and exploring the growing role of digital and AI-mediated environments in meaning-making. At the same time, the paper underscores the growing importance of metaphor awareness in language education as a means of strengthening learners’ interpretive and critical skills. We conclude that metaphor is a foundational cognitive and cultural resource - dynamic, adaptable, and central to meaning-making in diverse social interactions, and recommend future research on metaphors in digital and AI-mediated contexts, in language education, and in developing context-sensitive methodological frameworks.